Assessing the Legal Challenges in Prosecuting Gender-based Violence Cases: A Critical Analysis of Judicial Practices and Institutional Frameworks. - Florence Namuleme (Uganda Christian University, 2025)
This study critically examines the legal challenges in prosecuting gender-based violence (GBV) cases in Uganda, with a particular focus on the effectiveness of judicial practices and institutional frameworks. Despite the existence of a comprehensive legal framework including the Domestic Violence Act, the Penal Code Act, and international treaties like CEDAW, survivors face significant barriers, including low prosecution rates, skepticism and suspicion associated with SGBV, judicial stereotypes attributed to gender, lack of GBV courts for timely delivery of justice, pervasive societal stigma, victim-blaming, overlapping statutory and customary laws, under funding of judicial institutions, and sociocultural norms that blame victims and prioritize informal dispute resolution over justice, poverty, evidentiary limitations, and limited public awareness further exacerbate survivors’ inability to access justice. The study also identifies judicial bias, weak enforcement mechanisms, and inadequate victim support systems as key obstacles to successful prosecution. The research concludes that Uganda's legal and institutional responses to GBV remain insufficient in reality and practice and it requires urgent reform. It recommends the establishment of specialized courts, legal reform to address gaps in existing laws, training for justice personnel, increased funding and, improved victim support systems, and enhanced community sensitization. It also calls for a more collaborative, compassionate and effective justice system that recognizes the dignity and rights of all individuals, fostering an environment where survivors can seek justice without fear or shame. Addressing these barriers is essential for promoting accountability, protecting survivors’ rights, and advancing gender equality in Uganda.